PENGARUII CORPORATE GOWRNANCE TERIIADAP STRUKTUR MODAL DAN KINERJA PERUSAHAAI\: STUDI EMPIRIS PADA FAMILY BASINESS GROUP YANG TERDAFTAR DI BURSA EFEK JAKARTA - Freddy Iston Hasil Marbudi Pangaribuan (Jurnal Riset Manajemen dan Bisnis, 2007)
The aim of this research is to examine the effect of corporate governancet's internal mechanism that ls institutionii o*r"rriip, oi both firm performance and firm capital structure. To the extent, the moderating effect of managerial ownership on the relationship between institutional ownership,-fir* performance and capital structure wilt be examined as well.The sample of this research is drar,vn fro* companies within the big six family,owned business in Indonesia, which are listed at The Jakarta Stock Exchange fro* 1998 until 2005. Using the Moderated Regression Analysis (MRA),. the result shows that both institutional and managerial ownership fail to demonstrate the direct and moderated effect on both performance and capital structure. These findings suggest that the froil of economic, social and political circumstances create the "short term-focused" toward investment return. Moreover, the slow achiqement of collusion, corruption, and nepotism (KI< I) eradication has resulted in sudden-withdrawal of investor's investment. Hence, the internal control mechanism of corporate governance which is long-term focused and associated with KKI{ eradi cation cannot b e su cc es sfully impl em ent ed.Keywords: Institutional ownership, managerial ownership, performance,capital structure